A wearable aptamer nanobiosensor for non-invasive female hormone monitoring - Ye, Cui; Wang, Minqiang; Min, Jihong; Tay, Roland Yingjie; Lukas, Heather; Sempionatto, Juliane R.; Li, Jiahong; Xu, Changhao; Gao, Wei (Nature nanotechnology, 2024)
Personalized monitoring of female hormones (for example, oestradiol) is of great interest in fertility and women’s health. However, existing approaches usually require invasive blood draws and/or bulky analytical laboratory equipment, making them hard to implement at home. Here we report a skin-interfaced wearable aptamer nanobiosensor based on target-induced strand displacement for automatic and non-invasive monitoring of oestradiol via in situ sweat analysis. The reagentless, amplification-free and ‘signal-on’ detection approach coupled with a gold nanoparticle-MXene-based detection electrode offers extraordinary sensitivity with an ultra-low limit of detection of 0.14 pM. This fully integrated system is capable of autonomous sweat induction at rest via iontophoresis, precise microfluidic sweat sampling controlled via capillary bursting valves, real-time oestradiol analysis and calibration with simultaneously collected multivariate information (that is, temperature, pH and ionic strength), as well as signal processing and wireless communication with a user interface (for example, smartphone). We validated the technology in human participants. Our data indicate a cyclical fluctuation in sweat oestradiol during menstrual cycles, and a high correlation between sweat and blood oestradiol was identified. Our study opens up the potential for wearable sensors for non-invasive, personalized reproductive hormone monitoring. A reagentless, wireless, wearable aptamer nanobiosensor interfaced with a gold nanoparticle-MXene-based electrode enables the selective, automatic and non-invasive analysis of the female hormone oestradiol in sweat during menstrual cycles with subpicomolar sensitivity.